PENERAPAN METODE PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IX PADA PEMBELAJARAN AGAMA ISLAM (PAI) DI SMPT AR-ROSYID TULUNGAGUNG - Anisiya Gita Rahmadani Lutfi; Zainuddin, Mohammad Riza; Soeripto (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
Project Based Learning Using student-led projects or activities to impart knowledge is the most recent approach to education. In addition to this, Islamic religious education is an ally in the fight to instill moral principles and admirable character in the next generation of our country. The decrease in learning motivation among SMPT Ar-Rasyid Tulungagung's ninth graders prompted this investigation. So, to formulate the study topic, we need to know 1) how SMPT Ar-Rasyid Tulungagung's PAI classes benefit from using Project Based Learning, and 2) what challenges and opportunities arise from using this method. Class IX students at SMPT Ar-Rosyid Tulungagung will be the focus of this study, which seeks to improve their learning outcomes through the use of the Project Based Learning pedagogical approach and to detail the challenges and potential solutions to incorporating PBL into PAI instruction at the school. Implementation planning, observation, and reflection are the steps that make up the classroom action method (PTK), which is the research technique used. Using qualitative analysis, this study included nine students from SMPT Ar-Rosyid Tulungagung. The study found that compared to the first cycle's result of 71, the second cycle's result was 83.3. The results showed that students' comprehension of Islamic religious education content improved after using the Project Based Learning pedagogical approach.